VIGILÂNCIA DA DENGUE NO MATO GROSSO DO SUL: ANÁLISE GENÔMICA - Larissa Domingues Castilho de Arruda (2024)
Dengue, a prevalent vector-borne disease in Brazil, has triggered widespread urban outbreaks, posing a substantial risk to public health since its emergence in early 1916. Investigate the dynamics of dengue virus (DENV) serotypes circulating in different regions of the country. Brazil is crucial for implementing effective disease control and prevention measures. This descriptive and retrospective study covers the period 2021 and 2022 and involved 177 RNA samples with a positive result for arboviruses from the Central Public Health Laboratory of the state of Mato Grosso do Sul (LACEN MS). These samples originated from health services for the diagnosis of dengue and other circulating arboviruses, aiming at epidemiological surveillance. The samples received contained information about location, onset of symptoms, clinical manifestations and final classification. In response to the urgent need, we carried out an on-site training program in genomic surveillance, in collaboration with the Central Public Health Laboratory and the Department of Health of the state of Mato Grosso do Sul. This initiative resulted in the generation of 177 DENV genomic sequences collected between May 2021 and May 2022, during which more than 11,391 cases of dengue were reported in the state. We identified the co-circulation of two different dengue serotypes (DENV-1 and DENV-2) and observed the presence of distinct viral lineages within each genotype, indicating multiple events of introduction of different viral strains in the region. In phylogenetic analyses, the new DENV1 strains were classified as genotype V and formed four distinct clades (I-IV), with clades III and IV forming robust monophyletic groupings. In DENV2, they were classified into genotype III BR4 Clade 2, previously identified in the country in 2019. Integrating epidemiological data, our findings revealed temporal fluctuations in the relative abundance of different serotypes over several epidemic seasons, highlighting the complex and evolutionary dynamics of DENV2 transmission. DENV over time. These results emphasize the continued importance of surveillance efforts to monitor viral evolution, track transmission patterns, and guide public health interventions. Keywords: Dengue virus. Genomic surveillance. Phylodynamics. Epidemiology.